Community Acceptance of Nature-Based Solutions in the Delta of the Tordera River, Catalonia - Andrea Nóblega-Carriquiry; Hug March; David Sauri (Land, 2022)
Much has been debated regarding the environmental and economic aspects that conform the pillars of sustainability in nature-based solutions (NbSs). However, the social implications are lagging behind in both theory and practice. NbSs are not inherently socially and environmentally just and they might not work for or benefit everyone. On the contrary, they may lead to unequal environmental tradeoffs influencing therefore community acceptance. This research explored the different levels of community acceptance of NbSs in the Tordera delta (Catalonia) through structured interviews and Q-methodology with representative stakeholders. It pretended to contribute to more just NbS discussions by identifying variables of community acceptance through a socio-environmental perspective. The results exposed existing socio-economic and socio-spatial differences that cause unequal co-benefits and tradeoffs among stakeholders of the area. Three distinctive discourses were identified: (1) NbSs as an opportunity to re-naturalize the river; (2) the possibility of NbS implementation if aligned with the current socio-economic structure of the delta; and (3) the belief in a hybrid NbS future, combining grey infrastructure and NbSs. Building on those results and discussions, the paper reflected on a restructuration of the delta’s governance through further collaborative processes to seek a more socio-environmentally just and inclusive NbSs in the area.